Pengaruh Pengetahuan Dan Persepsi Nilai Terhadap Keputusan Menggunakan Produk Perbankan Syariah - Enur Hotimah; Dede NI; Sri Wahyuningsih; Ari MH; Eka Maulana (JPIES: Jurnal Pelita Ilmu Ekonomi Syariah, 2024)
This research aims to analyze and test how much knowledge and value influence decisions on the use of products in Sharia banking. This analysis uses independent variables namely knowledge and perception of value and dependent variables that are decisions using products in Sharia banking. The samples in this study are the villagers of Cikuya Tasikmalaya. The sampling technique used in this study is probability sampling with cluster sampling area i.e. by sampling techniques in groups sampling is done based on a specific group or area. Data collection was conducted with questionnaires distributed directly to 80 respondents. Statistical methods use description tests of each variable, validity and reability tests, classic assumption tests, simple linear regression analysis tests, multiple linear regression analysis tests with hypotheses tested using t and F tests with a 5% significance level. The results of this study show that the influence of knowledge partially affects the decision to use products in Sharia banking and the perception of value partially affects the decision to use products in Sharia banking. And simultaneously knowledge and perception of value significantly influenced the decision to use products in sharia banking by 33.2% while the remaining 66.8% was influenced by other variables that were not in this study.